Amateurs exhibit greater psychomotor efficiency than novices: evidence from EEG during a visuomotor task - Lu, Guo; Hagan, John Elvis; Cheng, Ming-Yang; Chen, Dong-Tai; Lu, Chieh-Ju; Lin, Fang-Yi; Chen, Li-Ju; Li, Dan; Wang, Kuo-Pin (Frontiers in Psychology, 2025)
IntroductionThe goal of this study was to examine the neural activities, which contribute to performance efficiency in the early stages of motor skill learning, such as amateur versus novice. To achieve this goal, electroencephalography (EEG) was employed to compare the differences in EEG power that can be used to assess neural excitability between amateur and novice golfers during a visuomotor task (i.e., golf putting task).Methods16 amateurs (9 females, 7 males, mean age = 20.81 ± 1.83; an intermediate skill level with an average handicap of 33 ± 5.68 and 3.81 ± 1.83 years of experience) and 16 novice golfers (9 females, 7 males, mean age = 22.25 ± 1.61; no prior experience in golf or formal training) were asked to perform a golf putting task while their EEG was recorded. During the warm-up session, each participant determined their individual putting distance, targeting a 40–60% success rate. Once established, participants were asked to perform 10 putts per block across 6 blocks in the experimental session.ResultsThe results of the study indicated that amateur golfers demonstrated: (1) higher Fz Theta power, (2) higher Fz, Pz, T7, T8 Alpha 2 power, (3) higher Mu 2 power, and (4) higher SMR power compared with novices during motor preparation. These findings suggest that amateur golfers exhibited reduced motor programming (as indicated by higher Alpha 2 power at Fz and Mu 2 power), reduced verbal-analytical engagement (higher T7 Alpha 2 power), reduced conscious perception of sensations (higher SMR power), reduced visuospatial processes (higher Alpha 2 power at Pz and T8), and enhanced cognitive control of sustained attention (higher Fz Theta power).DiscussionThese findings support the notion that the achievement of psychomotor efficiency involves the selective activation and inhibition of neuromotor processes. The study outcomes not only contribute to a broader understanding of the refinement of neuromotor processes during the transition from novice to amateur, but also specify neuromotor processes that can be categorized within the framework of psychomotor efficiency.